Study and application of holography system for mechanical stress and surface deformation - Kua, Hock Chuan (2004)
Holography is a technique to record information and reconstructs it in three dimensions. Although the technique was developed almost 40 years ago, it still possesses great potential and present rapid research in its application will continue. The aim of this project is to study various techniques of holography and the applications of holographic interferometry in mechanical stress and surface deformation measurement. Initially, a dark room and a vibration-free optical table are set-up. Low power He-Ne laser with output power of 1 mW and 10 mW are employed as light source. Various alignment techniques of holography setup are implemented and compared including Gabor holography, reflection holography, transmission holography, rainbow holography, data storage holography and double exposure holographic interferometry. In particular, the double exposure technique is applied to measure the Young's modulus of aluminum can and surface deformation of an object. Although the optical alignment is different for each technique, in general, they need to go through similar procedure: recording, developing, reconstruction and permanent record of hologram image. All the holograms are successfully developed and viewed in three dimensions. Double exposure hologram produces interference patterns which indicate the occurrence of deformation due to the stress given. The Young's modulus of the Aluminum can was measured to be (0.80 * 0.18) x 10' ~ m - ~ which is in the same order of magnitude with the mechanical measurement of (1.76 It 0.01) x 10' ~ m - ~ by the Universal Testing Machine by taking into account the calibration and measurement error. On the other hand, a surface deformation measurement system is developed and capable of detecting displacement up to 2.69 pm.